Incidence of occult cleft palate on prenatal magnetic resonance images obtained for non-cleft indications. Issue 5 (May 2023) - Resnick, C.M.; Paige, A.; Jindal, S.; Gordon, A.M.; Estroff, J.A.
Abstract: Prenatal diagnosis of craniofacial anomalies has improved family education and preparedness. Isolated cleft palate, however, remains difficult to identify sonographically. The aim of this study was to investigate the rate of incidental cleft palate identified on fetal magnetic resonance imaging (MRI) following the ultrasound detection of non-cleft abnormalities. This was a retrospective study of pregnant women who had fetal MRI performed between 2003 and 2017. To be included, the woman had to have been referred for fetal imaging for a non-cleft indication, with subsequent identification of an isolated cleft palate on MRI. Fetuses with a postnatal diagnosis of Robin sequence were excluded. The study sample included 30 women. Mean gestational age at MRI was 24 weeks 4 days± 38 days. Most referrals (76.7%) were for non-cleft craniofacial anomalies, of which micrognathia was the most common (63.3%). The annual incidence of occult cleft palate diagnosis was 0.4%, and a genetic syndrome was suspected based on imaging findings in 76.7%. Although rare, isolated cleft palate found incidentally on fetal imaging led to concern for a genetic syndrome in a high percentage of cases. This suggests that early referral for fetal MRI may provide critical information when sonographic fetal anomalies have been identified.